Respect for privacy from the Strasbourg perspective - Lorenc Danaj (Academicus, 2012)
Some of the most promising post-Cold War developments in Marxian thought have been stimulated by problems facing Marxists in Western Europe, to that extent they all seem to lay bare, intentionally or otherwise, the lacking of qualities, of Marx’s prediction. The most significant example of the failure of Marxist theory to be realised in practice is the persistent survival of the capitalist mode of production. The inevitable crisis foreseen by Marx, which would lead to revolution, failed to materialise and that claim is now itself historical, since capitalism has become the norm for social organisation in most of the world’s nations. By asking the question how capitalism can persist amid crisis, Gramsci, provided the most promising way of revision to the stunted Marxian orthodoxy. Today for us is important to ask whether Marxist analysis of neoliberal global strategy or globalisation and fragmentation invite reconsideration of the tendency on the part of many international relations scholarships to ignore and simply dismiss Marxism. It is also important to consider whether the significance of Marxist project of developing a critical approach to international politics, is but one way in which Marxism progressed beyond the traditional Anglo-American scholarship to IR.